Lactobacillus rhamnosus intake can prevent the development of Candidiasis - Leão, Mariella Vieira Pereira (2018)
Objective: This study aimed to investigate the influence of Lactobacillus rhamnosus intake on the development of candidiasis and cytokines release. Material and methods: Candida suspensions were inoculated into the oral cavity of experimentally immunosuppressed mice for candidiasis induction. The animals were divided into experimental groups: candidiasis with no probiotic intake (F), candidiasis with probiotic intake during Candida inoculation (FP), and candidiasis with probiotic intake 14 days before inoculation with Candida (FPP); and control groups: (C), (CP), and (CPP) without inducing candidiasis with probiotic intake in the same manner as groups F, FP, and FPP, respectively. After these periods, samples were collected from the oral cavity for yeast counts and, after euthanasia, the tongues of the animals were removed for histological analysis. Sera samples were also collected for analysis of IL-1 beta, TNF-alpha, INF-gamma, IL-12, IL-4, and IL-10. Results: FP group showed lower Candida counts in the oral cavity, and the presence of Candida was almost not detected in FPP group. In tissues, the counts of fungi were significantly lower in FPP group, followed by FP. Groups that consumed probiotics also had lower histological and inflammatory infiltrates compared to F. Cytokines analysis demonstrated low concentrations of TNF-α, IL-12, IL-4, and IL-10 in all the groups, and no statistical difference between them. The production of IL-6 could be better detected, and the experimental groups that consumed the probiotic showed significant lower levels of this cytokine. Conclusions: The results suggest that L. rhamnosus intake, especially preventively, may avoid or decrease the development of candidiasis in immunosuppressed mice. Clinical relevance: This work adds scientific evidences that probiotics intake can avoid the development of candidiasis.